Analysis of Service Quality Performance in Inter-City Public Transportation Modes in North Sumatra Province - Wan Habibi Rahman Barus; Nadiya Maharani; Nia Candrawati (Telkom University, 2026)
This study examines the decline in users of rail transportation services in North Sumatra Province, which decreased by 80% from 2017 to 2021, primarily due to reduced service quality performance. Service quality plays a crucial role in enhancing customer satisfaction and loyalty toward service provider companies. The study employs the SERVQUAL method to analyze the gap between customer expectations and perceptions of service quality provided by Damri rail and bus transportation services. A total of 21 variables were analyzed, consisting of 3 variables in the reliability dimension, 6 in tangibles, 4 in empathy, 4 in assurance, and 4 in responsiveness. The Customer Satisfaction Index (CSI) results show satisfaction levels of 59.03% for Damri train users and 65.30% for Damri bus users, both categorized as “fairly satisfied.” The analysis revealed that the largest service quality gap for train users lies in the tangible dimension with a value of –8.8696, and for bus users, also in the tangible dimension with a value of –7.2174. The top priority for service improvement in train services is the comfort and seating area (tangible dimension) with a gap value of –2.3913. Meanwhile, for bus services, the priority improvement variable is the punctuality of departure time (reliability dimension) with a gap value of –3.0000. The findings indicate that tangible and reliability dimensions require significant improvement to enhance overall service quality and customer satisfaction for Damri rail and bus transportation services.